Outcomes of implantable cardioverter‐defibrillator implantation in HIV‐infected patients: A single‐center retrospective cohort study - Narla, Venkata A.; Yang, Hannan; Li, Quefeng (Clinical cardiology (Mahwah, N.J.), 2022)
Background HIV‐infected individuals have a known increased risk of sudden cardiac death (SCD) compared to uninfected individuals. Implantable cardioverter‐defibrillators (ICDs) are standard therapy for preventing SCD; however, there is limited data on the outcomes of ICDs in HIV‐infected individuals. Hypothesis HIV‐infected subjects receive a higher number of appropriate ICD therapies than uninfected controls. Methods This is a retrospective cohort study of 35 consecutive HIV‐Infected patients and 36 uninfected controls matched by age, race, and gender who were treated at the University of North Carolina Medical Center in the outpatient or inpatient setting from 2014 to the present and had undergone ICD implantation. For HIV‐infected subjects, a multivariate Poisson regression analysis was performed to evaluate the association between covariates and ICD therapies. Results Among HIV‐infected subjects, the mean CD4 count was 582.5 cells/mm3 and 69% had an undetectable viral load. The median follow‐up was 6.4 years. HIV‐infected subjects had both a higher number of appropriate ICD shocks or antitachycardia pacing (ATP) therapy per person‐year as well as a higher number of inappropriate ICD shocks per person‐year than uninfected controls (1.512 vs. 0.590 and 0.122 vs. 0.0166, respectively, p < .001 for both comparisons). After multivariate adjustment, the presence of detectable/unsuppressed viral load at the time of ICD implantation was an independent predictor of both of the following in HIV‐infected subjects: (1) appropriate ICD discharge (p = .004), and (2) appropriate ICD discharge or appropriate ATP therapy (p < .001). Conclusion HIV‐infected subjects had a higher number of appropriate ICD discharge or ATP therapy per person‐year than matched uninfected controls.